Entry pathways of herpes simplex virus type 1 into human keratinocytes are dynamin- and cholesterol-dependent. - Elena Rahn; Philipp Petermann; Mei-Ju Hsu; Frazer J Rixon; Dagmar Knebel-Mörsdorf (PLoS ONE)
Herpes simplex virus type 1 (HSV-1) can enter cells via endocytic pathways or direct fusion at the plasma membrane depending on the cell line and receptor(s). Most studies into virus entry have used cultured fibroblasts but since keratinocytes represent the primary entry site for HSV-1 infection in its human host, we initiated studies to characterize the entry pathway of HSV-1 into human keratinocytes. Electron microscopy studies visualized free capsids in the cytoplasm and enveloped virus particles in vesicles suggesting viral uptake both by direct fusion at the plasma membrane and by endocytic vesicles. The ratio of the two entry modes differed in primary human keratinocytes and in the keratinocyte cell line HaCaT. Inhibitor studies further support a role for endocytosis during HSV-1 entry. Infection was inhibited by the cholesterol-sequestering drug methyl-β-cyclodextrin, which demonstrates the requirement for host cholesterol during virus entry. Since the dynamin-specific inhibitor dynasore and overexpression of a dominant-negative dynamin mutant blocked infection, we conclude that the entry pathways into keratinocytes are dynamin-mediated. Electron microscopy studies confirmed that virus uptake is completely blocked when the GTPase activity of dynamin is inhibited. Ex vivo infection of murine epidermis that was treated with dynasore further supports the essential role of dynamin during entry into the epithelium. Thus, we conclude that HSV-1 can enter human keratinocytes by alternative entry pathways that require dynamin and host cholesterol.